La Ley de Protección y Bienestar Animal a 7 años de su vigencia ¿Realmente se contempla el bienestar animal? - Franciskovic Ingunza , Beatriz (2023)
This article reflects on what animal welfare really implies and the progress that has been made in our country regarding the application of the oft-mentioned and little-known Animal Protection and Welfare Law. Before discussing or considering the legal category or condition of animals, it must be deepened and recognized what Animal Welfare means and understands, in order to better understand the situation and consideration of animals.